THE PLACE OF BRICS IN WORLD POLITICS - E. M. Astakhov (Vestnik MGIMO-Universiteta)
The unilateral model of international relations is not capable to execute global governance. The existing financial institutes serve only the interests of few highly developed countries. This situation does not satisfy developing countries. The latter put forward new approaches to the important task of reforming the world order system. BRICS countries will contribute to the elaboration of a new economic system based on equal to financial sources and trade markets. BRICS countries have the sufficient potential to become a new pole of political and economic influence free from geopolitical calculation and the temptation to impose their social models and political standards. Russia sees in BRICS an important place to discuss problems of international politics and world economy. At the same time Russia is interested in a dynamic economic cooperation with members of the group. Taking into consideration the current international situation, Russia will help to strengthen the political and economic position of BRICS. At the same time it is desirable to maintain a prudent policy of cooperation in both directions with East and with West.